1974
DOI: 10.1002/cpt1974162322
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of metolazone in normal subjects and in patients with cardiac or renal failure

Abstract: The pharmacokinetics of metolazane (Zaroxolyn)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…This has been shown for digoxin (Oliver, Tazman & Frederickson, 1973), hydrochlorothiazide (Anderson, Brettell & Aikawa, 1961;Beermann & Groschinsky-Grind, 1979) and metolazone (Tilstone, Dargie, Dargie, Morgan & Kennedy, 1974) in which the rate and/or extent of gastrointestinal absorption of these drugs were diminished in the heart failure patient. Crouthamel (1974Crouthamel ( , 1975, analyzing the date of Bellet, Roman & Boza (1971), has suggested that the rate and extent of oral quinidine absorption is also decreased in patients with congestive heart failure.…”
Section: Introductionmentioning
confidence: 78%
“…This has been shown for digoxin (Oliver, Tazman & Frederickson, 1973), hydrochlorothiazide (Anderson, Brettell & Aikawa, 1961;Beermann & Groschinsky-Grind, 1979) and metolazone (Tilstone, Dargie, Dargie, Morgan & Kennedy, 1974) in which the rate and/or extent of gastrointestinal absorption of these drugs were diminished in the heart failure patient. Crouthamel (1974Crouthamel ( , 1975, analyzing the date of Bellet, Roman & Boza (1971), has suggested that the rate and extent of oral quinidine absorption is also decreased in patients with congestive heart failure.…”
Section: Introductionmentioning
confidence: 78%
“…Physiologically this seems like an attractive approach to decongestion, one that is supported in the current heart failure practice guidelines, despite no randomized trials comparing combination diuretic therapy with a thiazide to loop diuretics alone 4. In fact, most studies examining metolazone use in HF are small, single‐center retrospective analyses without a control arm, published over 25 years ago, that focused on end points like urinary volume and sodium concentration as opposed to clinical outcomes 8, 10, 28, 29. Nevertheless, the cumulative existing evidence in only 350 patients does illustrate that metolazone produces a 3‐fold increase in natriuresis, increases weight loss and improves diuresis in patients who were previously not suitable for hospital discharge 7, 8, 9, 10, 28, 29, 30…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in sodium-and chloride reabsorption is seen in the proximal convoluted tubules without carbonic anhydrase inhibition [13][14][15]. Presumably as a consequence of the drug action in the proximal tubule, metolazone, in contrast to other thiazides, is able to produce a diuresis despite of a low glomerular filtration rate [9,16]. Severe congestive HF is often accompanied by a degree of renal failure due to low cardiac output making the use of metolazone attractive in fluid overload management in HF.…”
Section: Site Of Actionmentioning
confidence: 99%
“…The study included only three HF patients and apparently, no other studies have evaluated the fractional absorption of metolazone in HF patients. The rate of absorption of metolazone is lower in patients with cardiac or renal failure when compared to normal subjects [9]. Metolazone is excreted mainly in the urine, approximately 70-95% being unchanged [10,11].…”
Section: Absorption and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation